Life spring from a centre Islam shines through everything - Cheng, Yamin (The Other Press Sdn.Bhd., 2019)
This book looks at what happens when the centrality of God in the Muslim life is interrupted or broken. To do this, it focuses on the Malay society to see how that happens, what is coming out from this incident, and what lessons can be learned from it. This book also looks at the centrality of God in the identity of the Malaysian Chinese Muslims through the concept of Tian Ren He Yi or Harmony of Heaven and Human and attempts to show the compatibility of Islam to Chinese life. Islam in Malaysia has been seen as a Malay religion (by both Malays and Chinese) that has nothing to do with anything Chinese. As such, how can the Malaysian Chinese Muslims who are predominantly converts to Islam show that Islam can be expressed in a Chinese way? Young Muslims are the ones most affected with regard to their identity. In the midst of a world fragmented into pieces of identities, how do the young Malays see themselves as Muslims? This book tries to share with the young Malays regarding how they could gather the parts and pieces and put together an identity that they could relate to and make sense of themselves as Muslims in contemporary times